Global Politics and the Dynamics of Nigerian Foreign Policy: A Research Note on the Guiding Principles - EGWIM, Ambose Ihekwoaba (Socialscientia: Journal of Social Sciences and Humanities, 2024)
Various regimes since the 1999 return to democracy have tried to thinker or restructure Nigeria’s foreign policy guiding principles, necessitating the fears that Africa may no longer be the centerpiece of the nation’s foreign policy. This paper argues that Nigeria’s foreign policy review is imperative mainly because of four interlocking realities: globalization, the end of the Cold War, the decolonization of the African continent, the end of white minority rule in South Africa and the weak security and economic realities at home. The changes in the Nigerian foreign policy guiding principles are not necessarily a departure from the country’s traditional foreign-relations approach; however, while maintaining her Afrocentric strand, Nigerian foreign policy refocuses on Nigeria’s interest first. The moves entail that while Africa remains the centrepiece of Nigeria’s economic and foreign policy, things will be geared towards protecting a clear vision of national interests, unlike the former ’big brother’ approach.